2009
DOI: 10.1590/s1677-55382009000300001
|View full text |Cite
|
Sign up to set email alerts
|

Editor's comment: anti-neoplastic activity of curcumin in PCa

Abstract: The May -June 2009 issue of the International Braz J Urol presents important contributions from different countries, and as usual, the editor's comment highlights some papers. Doctor Leite and co-investigators, from Laboratory of Medical Investigation, Sao Paulo University, -cally, they used the LNCaP cell line and another prostate cell line developed in their own laboratory, PcBra1. A prostate cancer cell line was isolated from a localized prostate cancer with a Gleason score of 9 (4+5). After six passages, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The anti-carcinogenic properties of curcumin have been demonstrated in animal models and human studies have shown the chemo-preventive properties of curcumin against breast, prostate, colon, and lung cancer [44-50]. Curcumin’s anti-neoplastic activity, along with its low molecular weight and apparent lack of toxicity (use of up to 8 g/day), makes it an ideal foundation for the development of new, synthetic chemotherapeutic agents [51]. …”
Section: Introductionmentioning
confidence: 99%
“…The anti-carcinogenic properties of curcumin have been demonstrated in animal models and human studies have shown the chemo-preventive properties of curcumin against breast, prostate, colon, and lung cancer [44-50]. Curcumin’s anti-neoplastic activity, along with its low molecular weight and apparent lack of toxicity (use of up to 8 g/day), makes it an ideal foundation for the development of new, synthetic chemotherapeutic agents [51]. …”
Section: Introductionmentioning
confidence: 99%